Mini Riset Manajemen Humas Di Pondok Pesantren Tahfidz Qur’an Al Mansyur Bantul - Muhammad Fuad Al Azhar Rohman; Anna Dwi Lestari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Islamic boarding schools are the oldest education system currently compared to educational institutions that have appeared in Indonesia and have long been considered a product of Indonesian culture which has its own character. Islamic boarding schools are also very closely related to the existence of society. Therefore, the existence of Islamic boarding schools should be able to fulfill or demonstrate their existence to the demands of society. The existence of this community can be a supporting factor or a potential for the progress of the Islamic boarding school itself, but it can also be an inhibiting factor in its development.